Sustainable Power Generation : A Hybrid Approach using Solar Energy and Vertical Axis Wind Turbines - Soham Y Paradkar; Yogesh D Gawande; Durgesh Jadhav; Janardan Bagul; D.M.Bhatkar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This project explores the potential of combining solar energy and vertical axis wind turbines to generate electricity. By harnessing the power of both sun and wind, this hybrid system aims to provide a reliable and sustainable energy source. The system’s design and performance are evaluated, taking into account factors such as energy output, efficiency, and environmental impact. The results show that the hybrid system can significantly increase energy generation while reducing dependence on fossil fuels. This innovative approach has the potential to contribute to a cleaner and more sustainable energy future.